Occult Charm and Social Ills: Vernon Lee’s “A Wicked Voice” and George Du Maurier’s Castrated Texts - Kehler, Grace (Romanticism on the Net)

(untitled) (Université de Montréal, 2004)
AbstractThis article explores the late Victorian fascination with the defunct voice of the operatic castrato as manifest in two texts by Vernon Lee — Studies of the Eighteenth Century in Italy and “A Wicked Voice” — and in George Du Maurier’s Trilby. Each text imagines a revenant castrato, using the life and body of the violated singer as a source of enchantment and endless aesthetic speculation. Though these texts implicitly acknowledge their exploitive nature, they lack the self-mastery to resist the pleasure of making the surgically altered and socially wanting castrato serve perfection fantasies. Still, the representations of the revenant castrato bear with them a social and moral history that interrupts the pleasure of speculation and highlights the brutality of what art lovers have nominated as an ideal.